Effect of defensive pressure on international women's rugby sevens attacking skills frequency and execution - Griffin, J. A.; McLellan, C. P.; Presland, J.; Woods, C. T.; Keogh, J. W. L. (International Journal of Sports Science & Coaching, 2017)
The aim of the present study was to determine the effect of defensive pressure on the execution of attacking skills in international women's rugby sevens. Performance analyses were conducted across 42 training camp drills during the 2012-2013 season. Training camp sessions were recorded using a video camera positioned from an aerial perspective, with the attacking team's performance analysed during game-based drills. Technical skills assessed included pass type, pass accuracy, catching, evasive moves and line breaks. Results indicated that defensive pressure had a significant effect on a player's pass type, evasive moves and line breaks (p<0.05), but no significant effect on passing accuracy and catching skill (p>0.05). A cut-out pass (standard residual=3.3) was more likely to happen than expected by chance during no defence. An offload was more likely to occur than expected by chance during contested defence (standard residual=9.6). A line break (standard residual=4.7) and a swerve (standard residual=2.5) were more likely to happen than expected by chance during contested defence. Coaches should progressively overload the degree of defensive pressure during training. This may encourage the performance of non-conventional passes under contested defensive pressure, more closely reflecting the requisites of competition game-play. ABSTRACT FROM AUTHOR